2022
DOI: 10.1136/jitc-2022-004670
|View full text |Cite
|
Sign up to set email alerts
|

Real-world incidence and impact of pneumonitis in patients with lung cancer treated with immune checkpoint inhibitors: a multi-institutional cohort study

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) have improved survival and are increasingly used for non-small cell lung cancer. However, use may be limited by immune-related adverse events such as checkpoint-inhibitor pneumonitis (CIP). Literature estimates for CIP incidence are inconsistent. Real-world adherence to guidelines, clinical course, and healthcare utilization in the treatment of CIP has not been described in large cohorts.MethodsA combined claims and electronic health record database (TriNetX) was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 36 publications
1
22
1
Order By: Relevance
“…Some clinical trials and reports have shown that the incidence of CIP is approximately 5% ( 18 , 19 ). A multi-institutional cohort study recently has found that the risk of pneumonitis associated with PD-1/PD-L1 inhibitors compared with non-immunotherapy was 2.49% (95% CI: 1.50%-3.47%), and the median time to the onset of CIP was 3.9 months (IQR: 2.1-7.3) ( 20 ). In our study, the median time to the occurrence of CIP was 109 days (IQR: 30-221) after ICI treatment, and the incidence of CIP was approximately 18.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials and reports have shown that the incidence of CIP is approximately 5% ( 18 , 19 ). A multi-institutional cohort study recently has found that the risk of pneumonitis associated with PD-1/PD-L1 inhibitors compared with non-immunotherapy was 2.49% (95% CI: 1.50%-3.47%), and the median time to the onset of CIP was 3.9 months (IQR: 2.1-7.3) ( 20 ). In our study, the median time to the occurrence of CIP was 109 days (IQR: 30-221) after ICI treatment, and the incidence of CIP was approximately 18.5%.…”
Section: Discussionmentioning
confidence: 99%
“…5 6 However, irP is not uncommon in a real-world setting, and the incidence and mortality of irP is reported to range from 5% to 19% and from 2% to 27%, respectively. [7][8][9][10][11][12][13][14] Thus, cancer therapy is often interrupted because of treatment for irP, even if patients avoid a fatal outcome. 7 Treatment of irP has not been evaluated in any prospective trials, and there is no standardized, evidence-based treatment approach for irP.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…The staining positivity was determined by the following formula: overall score = percentage score  intensity score. The total score ranged from 0 to 12, with negative staining (0-1) and positive expression (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) of TCF-1. The cutoff score for PD-1 was ≥8% staining according to a previous study.…”
Section: Determination Of Tcf-1 Pd-1 Lag-3 and Tim-3 Ihc Cutoffsmentioning
confidence: 99%
“…Approximately 60% are lung adenocarcinomas, and most are diagnosed at a later stage 2,3 . Based on surgical resection findings, postoperative adjuvant therapy is usually required, which includes chemotherapy, radiotherapy, targeted therapy, and immunotherapy 4–8 . Recently, immunotherapy has been improved due to the rapid clinical development of effective immune checkpoint inhibitors (ICIs) such as T lymphocyte‐associated antigen‐4 (CTLA‐4), programmed cell death 1 (PD‐1), and its ligand (PD‐L1) 9,10 .…”
Section: Introductionmentioning
confidence: 99%